Bankruptcy Analysis Using the Altman Z-Score Method : Case Study on PT Garuda Indonesia, Tbk 2016 – 2019 - Winda Utami Siburian; Rahelsa Octaviana; Auna Syafitri; Dwi Saraswati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Bankruptcy is a state in which a company is unable to fulfil its financial obligations or a situation where the corporation initially functions but thereafter fails in business management. Bankruptcy is a state in which a firm lacks the money to operate its operation. The objective of the research is to identify the variables contributing to bankruptcy in PT. Garuda Indonesia. This research employs the Altman Z-score methodology using a bankruptcy calculation. This analysis indicates that the firm is at risk of bankruptcy, since its present assets from 2016 to 2019 are insufficient to meet its financial obligations. Companies must use deliberate, clear, and suitable measures to enhance operational cost efficiency. An inadequate business plan and human resources without a clear vision and goal for the organisation contribute to losses. This research seeks to evaluate the financial performance of PT Garuda Indonesia (Persero) Tbk from 2016 to 2019 using the Altman Z-Score model. The population and sample in this research consist of the complete financial statements of PT Garuda Indonesia (Persero) Tbk for the years 2016 to 2019. The findings of this research indicate that from 2016 to 2019, the bankruptcy rate at PT Garuda Indonesia (Persero) Tbk was unfavourable, as shown by a Z-Score below 1.10, signifying a state of bankruptcy. The most pronounced decrease was seen in the Working Capital to Total Asset ratio, particularly in 2019. This results from the annual growth in current obligations.